Analisis Pengendalian Persediaan Bahan Baku Menggunakan Metode Economic Order Quantity (EOQ) dan Safety Stock pada Caffe Street Zypo - Feri Irawan; Suseno . (GLOBAL SCIENTS PUBLISHER, 2026)
Raw material inventory control is a crucial aspect of maintaining operational continuity, particularly in the food and beverage industry, where demand tends to fluctuate. Caffe Street Zypo currently implements a manual inventory control system based on estimation, which may result in either excess inventory or stock shortages. This study aims to analyze the company's existing raw material inventory control system, determine the optimal order quantity using the Economic Order Quantity (EOQ) method, calculate the required Safety Stock, determine the Reorder Point (ROP), and evaluate inventory cost efficiency. The research employed the Economic Order Quantity (EOQ), Safety Stock, and Reorder Point (ROP) methods. Data were collected through observation, interviews, and documentation, including information on raw material demand, ordering costs, holding costs, and procurement lead time. The objects of this study consisted of the main raw materials, namely UHT milk, sweetened condensed milk (SCM), palm sugar, ice blocks, and plastic cups. The results indicate that the optimal order quantities (EOQ) are 202 units for UHT milk, 146 units for sweetened condensed milk, 125 units for palm sugar, 202 sacks for ice blocks, and 1,522 units for plastic cups. The Safety Stock calculation recommends maintaining 5 units of UHT milk as buffer inventory, while the Reorder Point (ROP) is determined at 19 units. Furthermore, the minimum Total Inventory Cost (TIC) obtained using the EOQ method is IDR 924,742. These findings demonstrate that the implementation of the EOQ, Safety Stock, and ROP methods can improve inventory control efficiency, reduce the risk of stock shortages, and minimize inventory costs compared with the inventory system currently applied by the company.